Urban ecosystem services and climate change: a dynamic interplay - Pandey, Bhanu; Ghosh, Annesha (Frontiers in Sustainable Cities, 2023)
Urban ecosystems play a crucial role in providing a wide range of services to their inhabitants, and their functioning is deeply intertwined with the effects of climate change. The present review explores the dynamic interplay between urban ecosystem services and climate change, highlighting the reciprocal relationships, impacts, and adaptation strategies associated with these phenomena. The urban environment, with its built infrastructure, green spaces, and diverse human activities, offers various ecosystem services that enhance the wellbeing and resilience of urban dwellers. Urban ecosystems offer regulatory services like temperature control, air quality upkeep, and stormwater management, plus provisioning like food and water. They also provide cultural benefits, promoting recreation and community unity. However, climate change poses significant challenges to urban ecosystem services. Rising temperatures, altered precipitation patterns, and increased frequency of extreme weather events can disrupt the functioning of urban ecosystems, impacting the provision of services. Heatwaves and urban heat island effects can compromise human health and energy demands, while changes in rainfall patterns can strain stormwater management systems and lead to flooding. Moreover, climate change can disrupt biodiversity and ecological processes, affecting the overall resilience and sustainability of urban ecosystems. To address these challenges, cities are adopting various adaptation strategies that recognize the interdependence between urban ecosystems and climate change. Green infrastructure interventions, such as the creation of urban parks, green roofs, and community gardens, aim to mitigate the impacts of climate change by enhancing the regulation of temperature, improving air quality, and reducing stormwater runoff. Additionally, urban planning and design approaches prioritize compact and walkable neighborhoods, promoting public transportation and reducing reliance on fossil fuels. Furthermore, engaging communities in the management of urban ecosystems and climate change adaptation measures is crucial for ensuring equitable distribution of ecosystem services and building social resilience. Therefore, the review article highlights a comprehensive understanding of the dynamic interrelationship between urban ecosystem services and climate change and their implications. By recognizing and integrating the contributions of urban ecosystems, cities can develop sustainable and resilient strategies to mitigate and adapt to climate change, ensuring the wellbeing and habitability of urban environments for present and future generations.